Non-thermal processes in bowshocks of runaway stars: Application to ζ Ophiuchi - Valle, María Elena del (2012)
Context. Runaway massive stars are O-and B-type stars with high spatial velocities with respect to the interstellar medium. These stars can produce bowshocks in the surrounding gas. Bowshocks develop as arc-shaped structures, with bows pointing to the same direction as the stellar velocity, while the star moves supersonically through the interstellar gas. The piled-up shocked matter emits thermal radiation and a population of locally accelerated relativistic particles is expected to produce non-thermal emission over a wide range of energies. Aims. We aim to model the non-thermal radiation produced in these sources. Methods. Under some assumptions, we computed the non-thermal emission produced by the relativistic particles and the thermal radiation caused by free-free interactions, for O4I and O9I stars. We applied our model to ζ Oph (HD 149757), an intensively studied massive star seen from the northern hemisphere. This star has spectral type O9.5V and is a well-known runaway. Results. Spectral energy distributions of massive runaways are predicted for the whole electromagnetic spectrum. Conclusions. We conclude that the non-thermal radiation might be detectable at various energy bands for relatively nearby runaway stars, especially at high-energy gamma rays. Inverse Compton scattering with photons from the heated dust gives the most important contribution to the high-energy spectrum. This emission approaches Fermi sensitivities in the case of ζ Oph.